Hydrothermal Synthesis and Gas Sensing of Monoclinic MoO3 Nanosheets - Teodóra Nagyné-Kovács; Levente Studnicka; István Endre Lukács; Krisztina László; Pawel Pasierb; Imre Miklós Szilágyi; György Pokol (Nanomaterials, 2020)
Effects of different reaction parameters in the hydrothermal synthesis of molybdenum oxides (MoO3) were investigated and monoclinic (β-) MoO3 was prepared hydrothermally for the first time. Various temperatures (90/210 °C, and as a novelty 240 °C) and durations (3/6 h) were used. At 240 °C, cetyltrimethylammonium bromide (CTAB) and CrCl3 additives were also tested. Both the reaction temperatures and durations played a significant role in the formation of the products. At 90 °C, h-MoO3 was obtained, while at 240 °C the orthorhombic (α-) MoO3 formed with hexagonal rod-like and nanofibrous morphology, respectively. The phase transformation between these two phases was observed at 210 °C. At this temperature, the 3 h reaction time resulted in the mixture of h- and α-MoO3, but 6 h led to pure α-MoO3. With CTAB the product was bare o-MoO3, however, when CrCl3 was applied, pure metastable m-MoO3 formed with the well-crystallized nanosheet morphology. The gas sensing of the MoO3 polymorphs was tested to H2, which was the first such gas sensing study in the case of m-WO3. Monoclinic MoO3 was found to be more sensitive in H2 sensing than o-MoO3. This initial gas sensing study indicates that m-MoO3 has promising gas sensing properties and this MoO3 polymorph is promising to be studied in detail in the future.